Isolation and Characterization of a Bacillus subtilis Mutant with a Defective N-Glycosidase Activity for Uracil-Containing Deoxyribonucleic Acid - Makino, Fumiko (1977)
Crude cell extracts of Bacillus subtilis 168T exhibit enzyme activity capable of releasing free uracil from phage PBS1 deoxyribonucleic acid (DNA) in the presence of ethylenediaminetetraacetate. By measuring the enzyme activity in 300 clones that emanated from mutagenized cells, we obtained a mutant strain that did not show this N-glycosidase activity. The mutant strain, designated as TKJ6901 (urg-1) exhibited no physiological abnormalities. We observed the intracellular action of the enzyme by following the fate of uracil-containing DNA in cells from wild-type and mutant cultures. When infection with phage PBS1 was allowed in the presence of chloramphenicol, extensive degradation of phage DNA was observed only in the wild-type cells. When bromouracil residues were converted to uracil residues by ultraviolet light irradiation in the presence of cysteamine, the DNA was extensively fragmented in the wild-type cells. These single-strand breaks were rejoined upon postirradiation incubation. In contrast, such fragmentation of the DNA was not observed in the mutant cells, indicating that the uracil residues were not removed from the DNA. This demonstrated that the N-glycosidase activity was involved in the excision of uracil in DNA. A transformation assay with four types of recipient strains with combinations of N-glycosidase and DNA polymerase I deficiencies indicated that DNA polymerase I was involved in the later steps of this base excision repair pathway initiated by the action of the N-glycosidase.